Os odontoideum: database analysis of 260 patients regarding etiology, associated abnormalities, and literature review - Menezes, Arnold H. (Frontiers in Surgery, 2023)
Ever since its first description of os odontoideum in 1886, the origin has been debated.Numerous case series and reports show both a possible congenital origin as well as secondary to craniovertebral junction (CVJ) trauma. We undertook a detailed analysis of 260 surgically treated cases to document first symptoms, age groups, radiographic findings, and associated abnormalities to better confirm the etiology. A literature search was made to correlate our findings.260 patients underwent surgical management of a referral database of 520 cases . All patients (260) underwent plain radiographs, myelo-tomography as needed until 1984, CT and MRI since then. History of early childhood (less than age 6 years) CVJ trauma was investigated including obtaining emergency department's initial radiographs from the referral and subsequent follow up. Associated radiographic and systemic abnormalities were noted and the atlas development followed.Patients ranged in age from 4 to 68 years, most seen between 10 and 20 years. There were 176 males and 86 females. Orthotopic os odontoideum was 24, dystopic 236. Associated abnormalities were 94/260; syndromic 73, Chiari I malformation 21. There were two sets of twins with spondyloepiphyseal dysplasia. Early childhood trauma 156/260, with initial normal radiographs (54/156) and subsequent anterior atlas hypertrophy and a smaller posterior C1 arch and development of os odontoideum was seen. There were two children who had MR documented initial CVJ trauma with later classical findings of os odontoideum and the atlas changes. Syndromic patients had an earlier presentation. The literature reviewed confirms the multifactorial etiology.Early presentation and associated abnormalities (Down syndrome, Klippel-Feil syndrome, Chiari I malformation, spondyloepiphyseal dysplasia, Morquio syndrome and others) and case reports of familial, hereditary and twin presentations make a strong point for congenital origin. Likewise the surgical complications are higher in the literature for syndromic patients (40%) as opposed to 15% otherwise. Early childhood trauma with documented normal odontoid and late os odontoideum formation proves trauma as an etiology also involving vascular changes to both the atlas and the os odontoideum formation. Associated abnormalities have an earlier presentation, and only seen in the nontraumatic origin.